2021
DOI: 10.1007/s00404-021-06022-w
|View full text |Cite
|
Sign up to set email alerts
|

Urogynecology in obstetrics: impact of pregnancy and delivery on pelvic floor disorders, a prospective longitudinal observational pilot study

Abstract: Purpose To assess changes in the pelvic floor anatomy that cause pelvic floor disorders (PFDs) in primigravidae during and after pregnancy and to evaluate their impact on women’s quality of life (QoL). Methods POP-Q and translabial ultrasound examination was performed in the third trimester and 3 months after delivery in a cohort of primigravidae with singleton pregnancy delivering in a tertiary center. Results were analyzed regarding mode of delivery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Childbirth is a natural result of pregnancy. Even under physiological conditions, childbirth affects the condition of the muscles and fascia of the abdomen and pelvic oor, leading to their thinning, especially under conditions of impaired broblast functions [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Childbirth is a natural result of pregnancy. Even under physiological conditions, childbirth affects the condition of the muscles and fascia of the abdomen and pelvic oor, leading to their thinning, especially under conditions of impaired broblast functions [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…As NW increases, the possibility of PFDs also increases. Previous studies have shown that excessive NW might harm PFM strength and was an independent risk factor for PFDs [ 49 , 50 ]. Stepwise regression analysis showed that NW rather than the NOF, had a negative effect on PFM strength, including rapid, tonic, and endurance contractions, which was contrary to the results of univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to increased and prolonged mechanical load and collagen changes, there is a decrease in the strength of the pelvic floor muscles [73]. Hormonal and mechanical changes during pregnancy lead to excessive stretching of ligament structures and pelvic floor muscles [74], connective tissue weakness and impairment of normal pelvic floor muscle function [74,75].…”
Section: Pelvic Floor Musclesmentioning
confidence: 99%